MULTI-LEO SATELLITE NETWORKS FOR INTEGRATED ACCESS AND BACKHAUL - Abdulkarim, Abubakar (School of Engineering and Digital Sciences, 2024)
Low Earth Orbit (LEO) Satellites have emerged as a promising solution to extend the coverage area of terrestrial networks, particularly in scenarios where ground users are located in remote or inaccessible areas. As such, forming a network over ground users with LEO satellites becomes essential to ensure reliable connectivity at desired data rates. This thesis focuses on investigating a LEO network for integrated access and backhaul (IAB) within fifth-generation (5G) systems, where LEO satellites serve as IAB nodes connecting to other IAB nodes for backhaul transmissions while acting as base stations (BSs) for ground users. LEO satellites offer rapid, low-latency connectivity, which is crucial for time-sensitive applications like remote surgery or autonomous vehicles where even slight delays could have significant repercussions. Positioned in a high altitude from the Earth’s surface, LEO satellites can achieve remarkably low latency levels, making them comparable to terrestrial networks in terms of responsiveness. Furthermore, the enhanced bandwidth capabilities afforded by LEO satellites position 5G networks optimally to handle the escalating data traffic and increasing number of connected devices effectively. In this work, A model is proposed for wireless multi-hop transmission in LEO satellite networks with integrated access and backhaul (IAB). This model supports ground users that can’t communicate directly with ground base stations (gNBs). The traffic flows for uplink and downlink transmissions are characterized using the channel capacity of both local access and backhaul links. LEO-Satellites serve as relay nodes facilitating the link between ground users and gNBs. Additionally, as LEO-Satellites form an interconnected network, they not only communicate with ground users but also engage in data exchange with neighboring LEO-Satellites. Consequently, in the IAB framework, LEO Satellites transform into IAB nodes, while gNBs act as IAB donors. Within this model, a path is defined by a series of connected LEO-Satellites, and each LEO-Satellite is tasked to deliver data between users and gNBs for uplink and downlink transmissions along the designated path. The proposed model is evaluated by analyzing end-to-end packet transmission delay and propagation delay. Analytical formulas for transmission delay in both the access and backhaul networks are derived, and extensive simulations are conducted to examine the system’s sensitivity to various parameters, providing insights into its performance under different scenarios. Furthermore, analytical expressions for outage probabilities are derived for both the backhaul link, consisting of inter-LEO satellite communication, and access networks connecting LEO satellites with ground users. The channel link in the access network is assumed to follow a Nakagami fading channel, while the backhaul network is primarily influenced by large-scale fading. Through numerical simulations, the impact of transmission rate and LEO-Sat transmit power on the system’s outage probability is analyzed, revealing trade-offs between data rate and reliability. To efficiently allocate transmit power to LEOs and support the specified data rates of ground users, an optimization problem is formulated and solved to minimize the total transmit power of LEOs
Keywords: Type of access: Embargo; LEO satellites; Integrated Access and Backhaul